2022
DOI: 10.4018/978-1-7998-9008-9.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Does Digital Transformation Impact Customer Experience?

Abstract: Nowadays, customers are expected to digitize their operations, and they start their journey anywhere, anytime, and from any device; they use multiple communication channels to interact with a business. Providing superior customer experience is considered a consumer-based strategy for attracting and retaining customers, and the customer experience plays a crucial role in digital transformation. To move the field forward, the purpose of this chapter is to review the literature on customer experience and develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Digital transformation has been identified as a critical factor in enhancing customer experience, with technology acting as both a catalyst and a facilitator for change. Studies have shown that digital transformation significantly impacts customer experience by enabling more personalized, efficient, and engaging interactions [1] . The integration of digital technologies in business operations has not only streamlined processes but also opened new avenues for customer engagement and satisfaction [2] .…”
Section: The Impact Of Digital Transformation On Customer Experiencementioning
confidence: 99%
See 3 more Smart Citations
“…Digital transformation has been identified as a critical factor in enhancing customer experience, with technology acting as both a catalyst and a facilitator for change. Studies have shown that digital transformation significantly impacts customer experience by enabling more personalized, efficient, and engaging interactions [1] . The integration of digital technologies in business operations has not only streamlined processes but also opened new avenues for customer engagement and satisfaction [2] .…”
Section: The Impact Of Digital Transformation On Customer Experiencementioning
confidence: 99%
“…The selection of literature for this review was guided by the relevance to the central themes of digital transformation and customer experience. A total of 12 papers were meticulously chosen based on their contributions to these topics, ensuring a diverse range of perspectives and findings [1][2][3][4][5][6][7][8][9][10][11][12] . These papers encompass various aspects of digital transformation, including its impact on customer experience, the tools and technologies used, and the challenges and opportunities it presents.…”
Section: Selection Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Second, customers today have higher expectations for digital experiences and companies that fail to deliver risk losing their customers to competitors. Digital transformation can help companies create seamless, personalized experiences that meet and exceed customer expectations (Shabani shojaei, 2022). Third, digital transformation can help businesses streamline processes, automate tasks and eliminate manual work.…”
Section: Introductionmentioning
confidence: 99%